Incidence and associated factors of developing second pelvic malignant neoplasms among prostate cancer patients treated with radiotherapy - Wang, Youbiao; Chen, Ru; Deng, Xinxi; Jiang, Xinghua (Frontiers in Oncology, 2023)
Objective: To identify risk factors of secondary pelvic malignant neoplasms (SPMNs) among prostate cancer (PCa) patients treated with radiotherapy. Simultaneously, population-based data were used to validate the high risk of SPMNs in PCa patients with radiotherapy.We identified male patients diagnosed with PCa (localized and regional) as the first primary cancer and pelvic malignant neoplasm (including bladder and rectal cancer) as secondary cancer from Surveillance, Epidemiology, and End Results database (1975-2020). An external validation cohort was obtained from the First Affiliated Hospital of Nanchang University. The Fine-Gray competing risk regression and Poisson regression were utilized to evaluate the risk of SPMNs development. Poisson regression was also performed to calculate the standardized incidence ratio (SIR). The Kaplan-Meier method was used to assess the overall survival (OS) of patients with SPMNs. Results: 89397 PCa patients treated with radiotherapy were enrolled. We identified associated factors of SPMNs, including age at diagnosis, race, year of diagnosis, marital status, radiation strategy and latency. In the multivariable competing risk regression model and Poisson regression model, a significantly higher risk of SPMNs development was observed in patients over 50 years(P<0.05), white patients(P<0.001), unmarried patients and treated with brachytherapy combined with external beam radiotherapy or brachytherapy(P<0.05). Patients treated with radiotherapy had a higher bladder and rectal cancer incidence than the general population. Patients who developed SPMNs showed poorer OS.We identified several risk factors associated with SPMNs and confirmed a relatively higher incidence of bladder and rectal cancer among PCa patients with radiotherapy. These results help tailor treatment and surveillance strategies.